Non-linear threshold effects of kinesiophobia on exercise adherence in older adults with COPD: a segmented regression analysis - Feng, Li; Ji, Hai Yan; Yang, Qing-Qing; Yao, Liang (Frontiers in Public Health, 2025)
ObjectiveTo explore the threshold effect of kinesiophobia on exercise adherence in older adult patients with chronic obstructive pulmonary disease (COPD).MethodsA cross-sectional survey was conducted on 357 older adults with COPD were assessed using standardized questionnaires for general information, exercise adherence, and kinesiophobia (Tampa Scale for Kinesiophobia, TSK). Multiple linear regression identified independent factors affecting adherence. A restricted cubic spline model analyzed the non-linear relationship between kinesiophobia and adherence.ResultsThe mean scores for exercise adherence and kinesiophobia were 30.9 ± 7.7 and 35.8 ± 10.7, respectively, with 59.9% of patients scoring above the clinical cutoff (>37) for significant kinesiophobia. Kinesiophobia (β = −0.51, p < 0.001), frequent hospitalizations (β = −0.25, p < 0.001), severe GOLD stage (β = −0.18, p < 0.001), and anxiety symptoms (β = −0.13, p = 0.001) were independent predictors of poorer adherence. A significant threshold effect was identified at a TSK score of 20. Below this threshold, kinesiophobia had no significant impact on adherence (β = −0.15, p = 0.312); above it, adherence declined sharply with increasing fear (β = −0.89, p < 0.001).ConclusionExercise adherence was suboptimal in older adults with COPD, who demonstrated substantial kinesiophobia. A TSK score of 20 points serves as a critical threshold, recommending its use for early identification of high-risk patients. Clinical management should prioritize patients with TSK scores ≥20, frequent exacerbations, and comorbid anxiety for targeted interventions.